State history. Grand Coulee Dam. Construction. Employment & wages. 1936-01-14 (1936)
1000 men are out of work. - Because of near-arctic weather, about one thousand men have been thrown out of work at Coulee dam site and will not be reemployed, probably, the MWAK company said, until about February 15 or 20.